Peran Guru dalam Peningkatan Mutu Pendidikan: Penting dan Genting! - Reggy Maulansyah; Dila Febrianty; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2023)
The aim of this study is to find out that teachers are a component in improving the quality of education. This study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from Prof. Prof.'s YouTube channel. Dr. Dasiem Budimansyah entitled